Teknologi Tepat Guna Pemurnian Minyak Kelapa Tradisional Di Desa Mengkalang Jambu Kabupaten Kubu Raya Kalimantan Barat - Maherawati; Iman Suswanto (Universitas Lancang Kuning, 2020)
Traditional coconut oil has the potential to be developed into commercial oil. These community service activities are a) coconut oil production practices, b) introduction of coconut oil refining technology and c) assessment of people's perceptions of coconut oil production. The variables used are the process of making oil, product quality, technology transfer and people's motivation to make oil. Questionnaire data were analyzed with contingencies to show the close relationship between variables and community groups. The results of the activity showed that there were two ways of making traditional coconut oil, using fresh coconut milk and fermented coconut milk. The resulting oil is crude coconut oil with a characteristic rancid odor, dark color and not durable. The process of oil production is a variable that shows real differences between young and old groups, while other variables are not significantly different. As many as 75% of young group respondents stated that the process of making coconut oil at a somewhat difficult to difficult level. The close relationship between the respondent group and the process of making coconut oil has high accuracy, which is 0.64. Improving coconut oil manufacturing techniques with the refining process can be one way to improve quality and efforts to support the commercialization of traditional coconut oil.